Juridiction et échelle : les « technicités » juridiques comme ressources pour la théorie - Mariana Valverde; Sandrine Brachotte (Clio@Themis)
Since the 1980 s, critical studies of law and space have fruitfully explored the insight that law’s mechanisms can be understood in part as mapping exercises. Existing work on law’s scales (especially that using a post-colonial studies frame) has delved into the qualitative as well as the quantitative dimensions of scale, thus exposing some key epistemological issues in law. This article moves the discussion forward by demonstrating that theoretical work on ‘scale’ – outside and inside legal studies – could benefit from studying specifically legal mechanisms such as ‘jurisdiction’. Recent work has shown that the various modes and rationalities of governance that coexist in every political-legal ‘interlegality’ are not necessarily tethered to any scale ; thus, exploring jurisdiction’s effects takes us beyond scale. As an example, the knowledge moves that constitute what in the USA is called ‘the police power of the state’ are briefly discussed. The fact that the gaze of police science/police regulation is not simply geographically local, but is rather specifically urban, shows the importance of understanding the complex governing manœuvres enabled by the legal game of jurisdiction – especially if work on ‘scale’ and jurisdiction is then supplemented by a consideration of the plural temporalities of governance, since temporality tends to become invisible both in analyses that privilege space and in the somewhat static diagrams of governance that make up the game of jurisdiction.